Occurrence of the PsbS and LhcSR products in the green alga Ulva linza and their correlation with excitation pressure - Zhang, Xiaowen (Plant physiology and biochemistry : PPB, 2013)
Copyright © 2013 Elsevier Masson SAS. All rights reserved.